2022
DOI: 10.3389/fnana.2022.809446
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of the Direct and Indirect Pathway Dichotomy in Mouse Caudal Striatum With Uneven Distribution of Dopamine Receptor D1- and D2-Expressing Neurons

Abstract: The striatum is one of the key nuclei for adequate control of voluntary behaviors and reinforcement learning. Two striatal projection neuron types, expressing either dopamine receptor D1 (D1R) or dopamine receptor D2 (D2R) constitute two independent output routes: the direct or indirect pathways, respectively. These pathways co-work in balance to achieve coordinated behavior. Two projection neuron types are equivalently intermingled in most striatal space. However, recent studies revealed two atypical zones in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 81 publications
(122 reference statements)
0
19
0
Order By: Relevance
“…Several possible reasons could explain all these differences between the tail and dorsolateral striatum. Firstly, expression of tyrosine hydroxylase is lower in the tail striatum (Miyamoto et al, 2019; Ogata et al, 2022). This finding, albeit in mouse, could be explained by a comparatively lower density of dopamine terminals in the tail striatum, which would lead to less spontaneous dopamine release and subsequent lower basal concentration (Liu et al, 2021; Rice et al, 2011) as well as smaller evoked dopamine release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several possible reasons could explain all these differences between the tail and dorsolateral striatum. Firstly, expression of tyrosine hydroxylase is lower in the tail striatum (Miyamoto et al, 2019; Ogata et al, 2022). This finding, albeit in mouse, could be explained by a comparatively lower density of dopamine terminals in the tail striatum, which would lead to less spontaneous dopamine release and subsequent lower basal concentration (Liu et al, 2021; Rice et al, 2011) as well as smaller evoked dopamine release.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, unlike the dorsolateral striatum which receives input from densely packed dopamine neurons in the SNc that branch extensively (Matsuda et al, 2009), the tail striatum is innervated by a more sparsely populated cluster of dopamine neurons in the SNL (Fu et al, 2012; González‐Hernández & Rodríguez, 2000). Furthermore, unlike the relatively homogenous dorsolateral striatum, studies have shown that the tail striatum comprises of multiple subdivisions, notably two broad ventral regions lacking either the D 1 or D 2 dopamine receptors (Gangarossa et al, 2013; Miyamoto et al, 2019; Ogata et al, 2022). These subdivisions also have different compositions of GABAergic and cholinergic interneurons, which, through cortico‐striatal input, can modulate basal dopamine (Abudukeyoumu et al, 2019; Lopes et al, 2019; Roberts et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about this division that could explain the disparity between TH expression and reduced dopamine release, largely because of its notable absence in previous tail striatum studies (e.g. Ogata et al., 2022). This discrepancy suggests additional local mechanisms modulating dopamine release are present in the dorsal tail striatum, but it remains to be seen what these are precisely.…”
Section: Discussionmentioning
confidence: 99%
“…Peak dopamine clearance velocity was also similar between most regions but was uniquely low in the intermediate division. We propose that this is as a result of the particularly low expression of DAT in this region (Ogata et al, 2022)…”
Section: Regional Variation In Dopamine Clearance In the Tail Striatummentioning
confidence: 91%
“…A PPTg lesion was thought to induce the hypoactivity of the STN and SNpr, and it was confirmed that a unilateral lesion of the PPTg could reverse the hyperactivity of the STN and SNpr in a 6-hydroxydopamine rat model ( 57 ). Moreover, a recent neuroanatomical study showed that the lateral part of the SNpr mainly received indirect pathway-related innervations ( 58 ). Combined with our finding that the neural activity of the lateral part of the SNpr was significantly reduced, it was proposed that the indirect pathway was impaired.…”
Section: Discussionmentioning
confidence: 99%